Knowledge, attitudes and decision-making preferences of men considering participation in the TROG RAVES Prostate Cancer Trial (TROG 08.03). Issue 1 (April 2016) - Tesson, Stephanie; Sundaresan, Puma; Ager, Brittany; Butow, Phyllis; Kneebone, Andrew; Costa, Daniel; Woo, Henry; Pearse, Maria; Juraskova, Ilona; Turner, Sandra
Abstract: Background and purpose: The RAVES (Trans-Tasman Radiation Oncology Group 08.03) randomised controlled trial (RCT), compares adjuvant radiotherapy with early salvage radiotherapy in men with high risk histopathological features at prostatectomy. The RAVES Decision Aid study evaluates the utility of a decision aid for men considering participation in the RAVES RCT. We report the RAVES Decision Aid study participants' attitudes and knowledge regarding RCTs, decision-making preferences and decisional-conflict. Materials and methods: Baseline questionnaires assessed knowledge and attitudes towards RCTs and RAVES RCT. Sociodemographic and clinical predictors of knowledge were examined. Involvement in decision-making and difficulties with the decision-making process were assessed using validated tools. Results: 127 men (median age = 63 years) were recruited through urologists ( n = 91) and radiation oncologists ( n = 36). Men preferred collaborative (35%) or semi-active (35%) decision-making roles. Most (>75%) felt the RAVES RCT was worthwhile and important with participation being wise. However, nearly half had high decisional-conflict regarding participation. Scores of objective knowledge regarding RCTs and RAVES RCT were low. Conclusions: Most men with high-risk histopathological features at prostatectomy desire active involvement in decision-making regarding further management. Despite positive attitudes towards RCTs and the RAVES RCT, there were gaps in knowledge and high decisional-conflict surrounding participation.